A Study on Teacher Correction Techniques in Assisting Student to Write English Composition - Elli Setiyo Wahyuni (Magister Scientiae, 2012)
This study was conducted to find out the teacher correction techniques on students writing composition. There are some techniques that can promote to correct the students composition, and the elements corrected show the errors of students’ sentence pattern commonly appear. Moreover, this study also answers the student perceptions toward the teacher correction. The students’ perceptions are the guideline for the teacher in choosing the most suitable techniques which match with their need for composition revision and the elements corrected also show how the ability of students in mastering sentences pattern, vocabulary, and another skills of languages.